Skrining Bakteri Simbion pada Lalat Buah (Drosophilla melanogaster) sebagai Kandidat Penghasil Senyawa Antibiotika - Armini Syamsidi; Arni Fitriyanti (Journal of Tropical Pharmacy and Chemistry, 2014)
Now the emergence of bacterial resistance to antibiotics is a national and global issues that have a significant impact on public health. We report the screening of bacterial symbionts in fruit flies (Drosophilla melanogaster) as a producer of new antibiotic compounds. This study aims to get antibiotic-producing bacterial symbionts in fruit flies (Drosophilla melanogaster). In this study used methods of isolation, purification and antibacterial testing using four test bacteria (Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Salmonella thyposa). Isolation of fruit flies (Drosophilla melanogaster) that uses peptone solution prepared dilutions to 10-9 and then purification is done by scraping the bacteria on NA medium by repeatedly to obtain pure isolates and subsequently antibacterial test. The results showed that the bacterial isolation 10-8 and 10-9 dilutions allegedly produce antibiotic-producing compound while the antibacterial test using test bacteria showed that the compound obtained from the insulation in the fruit fly (Drosophilla melanogaster) showed the compound to inhibit the growth of bacteria Escherichia coli and Staphylococcus aureus.